The Effect of Quadriceps Muscle Length on Maximum Neuromuscular Electrical Stimulation Evoked Contraction, Muscle Architecture, and Tendon-Aponeurosis Stiffness - Cavalcante, Jonathan Galvão Tenório; Marqueti, Rita de Cassia; Geremia, Jeam Marcel; Sousa Neto, Ivo Vieira de; Baroni, Bruno Manfredini; Silbernagel, Karin Gravare; Bottaro, Martim; Babault, Nicolas; Durigan, João Luiz Quagliotti (Frontiers in Physiology, 2021)
Muscle-tendon unit length plays a crucial role in quadriceps femoris muscle (QF) physiological adaptation, but the influence of hip and knee angles during QF neuromuscular electrical stimulation (NMES) is poorly investigated. We investigated the effect of muscle length on maximum electrically induced contraction (MEIC) and current efficiency. We secondarily assessed the architecture of all QF constituents and their tendon-aponeurosis complex (TAC) displacement to calculate a stiffness index. This study was a randomized, repeated measure, blinded design with a sample of twenty healthy men aged 24.0 ± 4.6. The MEIC was assessed in four different positions: supine with knee flexion of 60º (SUP60); seated with knee flexion of 60º (SIT60); supine with knee flexion of 20º (SUP20), and seated with knee flexion of 20º (SIT20). The current efficiency (MEIC/maximum tolerated current amplitude) was calculated. Ultrasonography of the QF was performed at rest and during NMES to measure pennation angle (θp) and fascicle length (Lf), and the TAC stiffness index. MEIC and current efficiency were greater for SUP60 and SIT60 compared to SUP20 and SIT20. The vastus lateralis and medialis showed lower θp and higher Lf at SUP60 and SIT60, while for the rectus femoris, in SUP60 there were lower θp and higher Lf than in all positions. The vastus intermedius had a similar pattern to the other vastii, except for lack of difference in θp between SIT60 compared to SUP20 and SIT20. The TAC stiffness index was greater for SUP60. We concluded that NMES generate greater torque and current efficiency at 60º of knee flexion, compared to 20º. For these knee angles, lengthening the QF at the hip did not promote significant change. Each QF constituent demonstrated muscle physiology patterns according to hip and/or knee angles, even though a greater Lf and lower θp were predominant in SUP60 and SIT60. QF TAC index stiffened in more elongated positions, which probably contributed to enhanced force transmission and slightly higher torque in SUP60. Our findings may help exercise physiologist better understand the impact of hip and knee angles on designing more rational NMES stimulation strategies.